Defining and documenting threats in the context of ill-treatment and torture - Pérez-Sales, Pau (Torture Journal, 2021)
Threats are a common feature of detention and interrogation settings and have long been regarded as a routine procedure. Despite their prevalence and propensity to amount to ill-treatment and torture, threats have not been systematically and thoroughly analysed in case documentation processes. Given a lack of understanding, threats have unduly been considered a form of “torture-lite” at best by some juridical actors. However, its effect as an instrument of coercion can be devastating – engendering states of fear and anxiety and forcing its subject to act against their will. There is an important lack of theoretical reflection on what threats are, what types exist and how they impact the survivor. In this editorial, we aim to partly fill this gap from a medical and psychological perspective, providing a framework of understanding that will hopefully improve conceptual and practical assessment, documentation and qualification.